The Effect of Empowerment and Religiosity on the Performance of Mosque-assisted MSEs in Yogyakarta - Wahyu Firmansyah; Indra Indra; Andang Heryahya (Journal La Sociale, 2024)
MSEs have an important role in regional and national economic growth. However, the current performance of MSEs is not optimal due to the limitations they face. So there needs to be a deeper analysis of empowerment and religiosity in maximizing MSE performance. This research aims to analyze the influence of empowerment and religiosity on MSE performance. The data analysis method in this research uses Structural Equation Modeling (SEM) and is processed using Partial Last Square (PLS) analysis and Package for the Social Sciences (SPSS). The research sample used in this research was 137 MSEs assisted by mosques in Yogyakarta. The data used in this research is primary data, namely it comes from statements presented in the form of a questionnaire survey given to target respondents. The research results show that empowerment has an effect but is not significant on the performance of MSEs assisted by mosques in Yogyakarta. Meanwhile, religiosity has a significant effect on the performance of MSEs assisted by mosques in Yogyakarta.